Hierarchical matrices : a means to efficiently solve elliptic boundary value problems - Bebendorf, Mario (Lecture Notes in Computational Science and Engineering, 2008)
This book presents both the algorithmic aspects of hierarchical matrices as well as their theoretical background. It contains the existing approximation theory for elliptic problems including partial differential operators with nonsmooth coefficients.